Allogeneic Hematopoietic Stem Cell Transplantation for Congenital Immune Dysregulatory Disorders - Bakhtiar, Shahrzad; Fekadu, Julia; Seidel, Markus G.; Gambineri, Eleonora (Frontiers in Pediatrics, 2019)
Primary immunodeficiency disorders (PID) affecting immune regulation and mechanisms of self-tolerance have become more visible through recent years. Patients often suffer from treatment refractory multi-organ autoimmunity and complications of long term immune suppressive treatment. There is cumulative evidence for allogeneic stem cell transplantation (alloHSCT) as a curative treatment option for severly affected patients by this disease category. Nevertheless, the underyling detailed pathomechanisms of most of these newly described diseases are not fully understood and often without a reliable genotype-phenotype correlation. Predictive and stratification-relevant tools are not established yet. In this review, we provide a literature-based update on indications and outcomes of alloHSCT for congenital immune dysregulative PID.